HEAT AND MASS TRANSFER IN RADIATIVE CASSON FLUID FLOW CAUSED BY A VERTICAL PLATE WITH VARIABLE MAGNETIC FIELD EFFECT - Vijayaragavan, R. (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
The aim of the present study is to investigate influence of variable magnetic field, heat and mass transfer in radiative Casson fluid flow past an infinite vertical porous plate. The governing equations of the flow, heat and mass transfer are transformed into a system of nonlinear ordinary differential equations and solved analytically by the perturbation technique with matlab package. The results obtained show that the velocity, temperature and concentration fields are appreciably influenced by the chemical reaction, thermal stratification and magnetic field. It is observed that the thermal radiation and magnetic field decreases the velocity, temperature and concentration profiles. There is also considerable effects of magnetic field and chemical reaction on skin friction coefficient and Nusselt number.